The American Jewish Community - Burstein, Paul (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This course is about the Jewish community in the United States–the many ways in which Jews met the challenge of life here. We will study Jewish migration to the U.S.; how Jews struggled to adapt Judaism to life in their new country; how they created organizations to help each other, to educate their children, and maintain their culture; how anti-Semitism and the fear of anti-Semitism affected their approach to American life; and how they contributed to American life in many areas, from the economy to the development of ideas about what it means to be an American. We will consider conflicts in the Jewish community over how to deal with life in the U.S., and the hopes and fears of the community about what the future will bring.